2020
DOI: 10.1007/s40629-020-00125-7
|View full text |Cite
|
Sign up to set email alerts
|

Dietary implications in acetylsalicylic acid intolerance

Abstract: Summary Background Acetylsalicylic acid (ASA) may cause difficult-to-treat symptoms of the airways, skin, or gastrointestinal tract in hypersensitive patients. Due to the chemical relationship between salicylic acid and ASA, a role of a low-salicylate diet has been discussed. Methods This review evaluates whether low salicylate diets are meaningful from an allergological or nutritional–physiological perspective. Results The body’s arachidonic acid metabolism plays a crucial role in the pathogenesis of ASA in… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…The Working Group concluded that reducing salicylate intake in the treatment of ASA hypersensitivity has no pathophysiological basis and may cause risks of nutritional deficiencies. Therefore, this type of diet is not recommended [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…The Working Group concluded that reducing salicylate intake in the treatment of ASA hypersensitivity has no pathophysiological basis and may cause risks of nutritional deficiencies. Therefore, this type of diet is not recommended [ 43 ].…”
Section: Discussionmentioning
confidence: 99%